nextMONARCH Phase 2 randomized clinical trial: overall survival analysis of abemaciclib monotherapy or in combination with tamoxifen in patients with endocrine-refractory HR + , HER2- metastatic breast cancer - Hamilton, Erika; Cortes, Javier; Ozyilkan, Ozgur; Chen, Shin-Cheh; Petrakova, Katarina; Manikhas, Aleksey; Jerusalem, Guy; Hegg, Roberto; Huober, Jens; Zhang, Wei; Chen, Yanyun; Martin, Miguel (Breast cancer research and treatment, 2022)
PURPOSE: Resistance to endocrine therapy poses a major clinical challenge for patients with hormone receptor-positive (HR +), human epidermal growth factor receptor 2-negative (HER2-) metastatic breast cancer (MBC). We present the preplanned 24-month final overall survival (OS) results, alongside updated progression-free survival (PFS), and objective response rate (ORR) results. METHODS: nextMONARCH is an open-label, controlled, randomized, Phase 2 study of abemaciclib alone or in combination with tamoxifen in women with endocrine-refractory HR + , HER2- MBC previously treated with chemotherapy. Patients were randomized 1:1:1 to: abemaciclib 150 mg and tamoxifen 20 mg (A + T), abemaciclib 150 mg (A-150), or abemaciclib 200 mg and prophylactic loperamide (A-200). OS was the main prespecified secondary endpoint. PFS, ORR, and safety at 24 months were compared to previously reported primary analysis results. RESULTS: Of the 234 patients enrolled, 12 were receiving study treatment at data cutoff (28Jun2019). Median follow-up was 27.2 months. Median OS was 24.2 months in the A + T arm, 20.8 months in A-150, and 17.0 months in A-200 (A + T versus A-200: HR 0.62; 95%CI [0.40, 0.97], P = 0.03 and A-150 versus A-200: HR 0.96; 95%CI [0.64, 1.44], P = 0.83). PFS and ORR results at 24 months were consistent with the primary analysis. The safety profile corresponded with previous reports. CONCLUSION: The addition of tamoxifen to abemaciclib demonstrated greater OS benefit than monotherapy. This study confirmed the single-agent activity of abemaciclib in heavily pretreated women with endocrine-refractory HR + , HER2- MBC, as well as the previously reported primary PFS and ORR results, with no new safety signals observed. Trial Registration ClinicalTrials.gov Identifier: NCT02747004.
Keywords: Humans; Aminopyridines; Benzimidazoles; Female; protokoly protinádorové kombinované chemoterapie; Tamoxifen; lidé; Overall survival; HER2-negative; Hormone receptor-positive; doba přežití bez progrese choroby; benzimidazoly; tamoxifen; MBC; Breast Neoplasms; ženské pohlaví; Antineoplastic Combined Chemotherapy Protocols; Endocrine therapy; nádory prsu; aminopyridiny; Cyclin-dependent kinase 4 and 6; Progression-Free Survival